Tratamento de imprecisão na geração de árvores de decisão - Lopes, Mariana Vieira Ribeiro (Universidade Federal de São Carlos, 2016)
Inductive Decision Trees (DT) are mechanisms based on the symbolic paradigm of machine learning which main characteristics are easy interpretability and low computational cost. Though they are widely used, the DTs can represent problems with just discrete or continuous variables. However, for some problems, the variables are not well represented in this way. In order to improve DTs, the Fuzzy Decision Trees (FDT) were developed, adding the ability to deal with fuzzy variables to the Inductive Decision Trees, making them capable to deal with imprecise knowledge. In this text, it is presented a new algorithm for fuzzy decision trees induction. Its fuzification method is applied during the induction and it is inspired by the C4.5’s partitioning method for continuous attributes. The proposed algorithm was tested with 20 datasets from UCI repository (LICHMAN, 2013). It was compared with other three algorithms that implement different solutions to classification problem: C4.5, which induces an Inductive Decision Tree, FURIA, that induces a Rule-based Fuzzy System and FuzzyDT, which induces a Fuzzy Decision Tree where the fuzification is done before tree’s induction is performed. The results are presented in Chapter 4.
Keywords: Árvore de decisão indutiva; Árvore de decisão Fuzzy; Problemas de classificação; Sistemas Fuzzy baseados em regras; Sistemas Fuzzy de classificação; Inductive decision tree; Fuzzy decision tree; Classification problems; Rule-based Fuzzy systems; Fuzzy classification systems; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO